Comparative Characteristics of Methods for Constructing Complete Removable Denture - Ruziyeva Sitora Sapar qizi (Zien Journals, 2022)
Study of removable dentures designs and features of occlusal relationships, taking into account the current level of development of gnat ology
Keywords: gnat ology; acrylic prostheses; complete removable denture; vomiting reflex